The Construction of Passive Verbs in Central and Banyumas Javanese: A Study of Typology - Kartika Eva Rahmawati; Made Mahadipa Budi. S (Prodi Tadris Bahasa Inggris, 2022)
Typology is a language study that is used to classify the characteristics or behaviors contained in the Central Javanese and Banyumas languages. This study discusses how the construction of passive verbs in Central Javanese and Banyumas languages ​​and how to group them based on the characteristics of passive sentences in general. The method used is the listening and note-taking method with respondents who are native speakers of the two languages. This research reveals that there are at least four language characteristics discussed, such as; the use of prefixes dak- kok-, and di- in Central Javanese and tek-, kok-, and di- in Banyumas Javanese and how the rules are used. Then, this study also explains how the change in the form of the verb from the original 'colong' or 'take' to 'tekcolong' or 'taken', and it proves that the subject in both languages ​​can be erased. The fourth characteristic is discussing the sound changes that result from passivation in Central Javanese and Banyumas.